Innate immunity and natural autoantibodies - Mouthon, Luc (Henry Stewart Talks, 2007)
Host defense mechanisms, Innate immunity: first line of defense, Physiological autoreactivity, Autoimmunity, Immunological tolerance, Self-reactive B and T lymphocytes, Natural autoantibodies, Origins of natural autoantibodies, Selection of antibody repertoires, Sources of autoantigens, Receptor editing, Differences between natural and pathogenic autoantibodies, Regulatory mechanisms that control the expression of natural autoantibodies, Functions of natural autoantibodies, Failure of control mechanisms is responsible for the occurrence of autoimmune diseases
Archived at 2018/05/31